(untitled) (Fiep Bulletin - online, 2013)
the mechanical ventilator is a respiration mechanism that can maintain ventilation and oxygen liberation for a prolonged period of time on patients with respiratory insufficiency. OBJECTIVES: to observe the precautions employed by the nursing team related to mechanical ventilator and to identify whether these precautions follow the CDC’s (2004) guidelines. METHODOLOGY: exploratory descriptive and quantitative study, performed on an ICU and emergency sector in an institution in the city of Natal-RN. The population consisted of 12 nurses and 38 nursing technicians. RESULTS: in the studied period 35 ventilators were assembled; 25 were not cleaned and disinfected prior to assembly; 21 were not assembled with aseptic technique; 29 were tested and among these, on 27 the test lung was not sterile. On 27 ventilators, the professionals used non-sterile materials to protect the Y connection; 18 were not labeled with name and date after assembly. 26 were assembled by nurses and 09 by nursing technicians; on 30 ventilators, the humidifiers were empty until installation; 29 were tested in the time of use; among these, on 26 the lung was not sterile; on 23, sterile water was used to fill the humidifiers. From 113 times when a check was made to see whether it had condensed in the circuit, on 87 condensation was present; among these, on 70 it was discarded. On 52 occasions hands were sanitized after extracting condensation. On 69 occasions in which humidifier water was refilled, on 58 it was already sterile. Regarding water change, this practice was not performed. CONCLUSION: the data point to a need of intensifying educational activities that promote behavior change on these professionals, thus improving the quality of assistance and prevention of nosocomial infection.